Computational analysis of non-isothermal temperature distribution on natural convection in nanofluid filled enclosures - Öztop, Hakan Fehmi; Abu-Nada, Eiyad; Varol, Yasin; Al-Salem, Khaled (Academic Press Ltd- Elsevier Science Ltd, 2011)
In this study, the problem of steady state natural convection in an enclosure filled with a nanofluid has been analyzed numerically by using heating and cooling by sinusoidal temperature profiles on one side. The governing partial differential equations, in terms of the dimensionless stream function-vorticity and temperature, are solved numerically using the finite volume method for various inclination angles 0 degrees <= phi <= 90 degrees, different types of nanoparticles (TiO2 and Al2O3) and fractions of nanoparticles 0 <= phi <= 0.1, whereas the range of the Rayleigh number Ra is 10(3)-10(5). It is found that the addition of nanoparticles into water affects the fluid flow and temperature distribution especially for higher Rayleigh numbers. An enhancement in heat transfer rate was registered for the whole range of Rayleigh numbers. However, low Rayleigh numbers show more enhancement compared to high Rayleigh numbers. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Nanofluid; Enclosure